2022
DOI: 10.3389/fmicb.2022.875323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Altitude on the Digestion Performance, Serum Antioxidative Characteristics, Rumen Fermentation Parameters, and Rumen Bacteria of Sanhe Heifers

Abstract: The production efficiency of dairy cows is affected by altitude, with lower efficiency reported at higher altitudes. However, only a few studies have investigated the digestion performance, serum antioxidative characteristics, rumen fermentation performance, and rumen bacteria of Sanhe heifers at different altitudes. Therefore, in this study, we explored the effects of altitude on these aspects of Sanhe heifers. We evaluated the effects of altitude on the apparent digestibility of nutrients, serum antioxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…In a previous study, we showed that different altitudes affect the rumen bacterial diversity of Sanhe heifers [21]. Changes in rumen microbiota structure may further affect differences in rumen metabolism.…”
Section: Introductionmentioning
confidence: 82%
“…In a previous study, we showed that different altitudes affect the rumen bacterial diversity of Sanhe heifers [21]. Changes in rumen microbiota structure may further affect differences in rumen metabolism.…”
Section: Introductionmentioning
confidence: 82%
“…In previous studies, we found that Jersey cattle showed adaptations to high altitude areas at both the miRNA and proteome levels ( Kong et al, 2019 ), illustrating adaptive mechanisms through up-regulation of amino acid metabolism and sphingolipid metabolism ( Kong et al, 2021 ). Zhang et al (2022) found that rumen fermentation and bacteria characteristic of highland Sanhe heifers had a lower acetate-to-propionate ratio as alternative hydrogen electron acceptors for CH 4 mitigation, a lower relative abundance of Actinobacteria, and higher relative abundance of Spirochaetae than that in rumen of lowland heifers. Cumulatively, these studies indicated that cattle introduced to the plateau also showed adaptations in phenotype and rumen fermentation microbiota.…”
Section: Overview Of Introduced Ruminants On the Qinghai–tibetan Plateaumentioning
confidence: 93%
“…In addition, low oxygen partial pressure, high altitude, strong UV radiation, Low precipitation, and poor forage availability on the alpine rangelands all present physiological challenges for its fauna ( Long et al, 1999 ; Yao et al, 2012 ; Liu et al, 2016 ; Friedrich and Wiener, 2020 ; Jing et al, 2022 ). Despite the challenges to husbandry associated with the need for enhanced adaptation, several domesticated ruminants have also been successfully introduced to the alpine pasture regions for meat and dairy production, such as hybrid sheep, goats, and cattle ( Huang et al, 2016 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sanhe cattle have rough feeding tolerance (Hu et al, 2019), strong disease resistance (Usman et al, 2017), and stable genetic performance. In previous reports, we introduced Sanhe cattle to an altitude of 3,650 m in Tibet and observed improved nutrient digestibility, indicating that Sanhe cattle exhibit strong adaptability to highaltitude environments (Zhang X. et al, 2022). However, the effects of feeding regimens on the composition and functions of gut microbiota in Sanhe heifers have not been explored.…”
Section: Introductionmentioning
confidence: 95%